2010
DOI: 10.3917/pox.091.0133
|View full text |Cite
|
Sign up to set email alerts
|

Les effets dissimulés du travail sur la santé de populations au chômage : le cas des contrats aidés dans le dispositif du RMI

Abstract: Résumé L’article propose de s’intéresser aux catégories de travailleurs relevant de contrats aidés réalisés dans le cadre des politiques d’insertion. Ces candidats à l’emploi aidé ont connu des parcours de déclassement, des trajets professionnels discontinus, instables, ponctués de périodes de chômage de plus en plus longues avant l’entrée dans les dispositifs de l’aide sociale, dont le RMI, aujourd’hui le RSA, constitue la figure emblématique. Usuellement considérés à la marge de l’emploi ordinaire, ces contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…), vibrations are some of the many conditions that have been identified as causing pain and hampering return to work [ 59 , 60 ]. In parallel, it is commonly accepted that professional inactivity contributes to decreased physical health [ 61 , 62 ]. In our study, we showed that inactive PSPS-T2 patients presented higher levels of pain intensity and functional disability than active ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), vibrations are some of the many conditions that have been identified as causing pain and hampering return to work [ 59 , 60 ]. In parallel, it is commonly accepted that professional inactivity contributes to decreased physical health [ 61 , 62 ]. In our study, we showed that inactive PSPS-T2 patients presented higher levels of pain intensity and functional disability than active ones.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of work translates into a loss of self-esteem, causes isolation, loss of a network of help and essential social support [ 72 ]. In addition, it has been reported that professional inactivity contributes to a decrease in the mental and physical health of individuals [ 61 , 62 ]. Taken together, these findings suggest that “Adapted Professional Activity” should be considered as a therapeutic approach within the health promotion framework for unemployed PSPS-T2 patients [ 73 ], and could be proposed by extension in every chronic disability.…”
Section: Discussionmentioning
confidence: 99%
“…sont également sensiblement meilleures pour les femmes à leur compte (que pour les salariées). Il est difficile d'interpréter ces résultats de façon causale, car des mécanismes d'auto-sélection ou du type « effet du travailleur sain » sont probablement à l'oeuvre (FRIGUL, 2010 ;TROTZIER, 2005). Il reste que les non-salariées semblent accorder une valeur supérieure à leur emploi que les salariées.…”
Section: Les Femmes Non Qualifiées : Une « Indépendance » éConomiquemunclassified
“…Other disciplines emphasize the selection aspect when using the concept: "a worker only occupies a position if his health allows it" (GOLLAC, VOLKOFF, 2006, p. 7). The HWE is described as a joint process of job selection and exclusion that is simultaneously psychological and physical (FRIGUL, 2010). There are some social aspects to the selection process.…”
mentioning
confidence: 99%
“…For example, some authors indicate that leaving a job depends not only on a worker's state of health, but also on his ability to find another job (SIRVEN, SERMET, 2009). Examining the reciprocal influences of work and health through longitudinal studies 1 has shown that the direction of causality between job and good health has not been established (FRIGUL, 2010). For sociologists, the HWE is not merely a statistical bias, it is also a social process that takes many forms through time, including but not limited to selection screening, mid-career expulsion, and earlier career change.…”
mentioning
confidence: 99%